2019
DOI: 10.1158/1055-9965.epi-18-0542
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiomes of Pancreatic and Duodenum Tissue Overlap and Are Highly Subject Specific but Differ between Pancreatic Cancer and Noncancer Subjects

Abstract: Background: In mice, bacteria from the mouth can translocate to the pancreas and impact pancreatic cancer progression. In humans, oral bacteria associated with periodontal disease have been linked to pancreatic cancer risk. It is not known if DNA bacterial profiles in the pancreas and duodenum are similar within individuals. Methods: Tissue samples were obtained from 50 subjects with pancreatic cancer or other conditions requiring foregut surgery at the Rhode Island Hospital (RIH), and from 34 organs obtained … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
150
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(160 citation statements)
references
References 54 publications
8
150
0
2
Order By: Relevance
“…One study found that individuals who had pancreatic tissue sampled after foregut surgery had a higher prevalence of Kluyvera (genus within the Enterobacteriaceae family) compared to pancreatic tissue from deceased controls; however, when comparing pancreatic cancer tissue to deceased control pancreatic tissue, Salmonella , Enterobacter , and Raoultella (genera within the Enterobacteriaceae family) had a lower prevalence. Similar to our results, this study also found a higher prevalence of Bacteroides (genus within the Bacteroidaceae family) in pancreatic cancer tissue compared to deceased control pancreatic tissue …”
Section: Discussionsupporting
confidence: 91%
“…One study found that individuals who had pancreatic tissue sampled after foregut surgery had a higher prevalence of Kluyvera (genus within the Enterobacteriaceae family) compared to pancreatic tissue from deceased controls; however, when comparing pancreatic cancer tissue to deceased control pancreatic tissue, Salmonella , Enterobacter , and Raoultella (genera within the Enterobacteriaceae family) had a lower prevalence. Similar to our results, this study also found a higher prevalence of Bacteroides (genus within the Bacteroidaceae family) in pancreatic cancer tissue compared to deceased control pancreatic tissue …”
Section: Discussionsupporting
confidence: 91%
“…Geller et al [29] reported that 15% (3/20) of normal pancreatic tissues contain bacterial DNA via qPCR detection. In both PDAC and noncancer patients, similar bacterial profiles were detected at different sites of the pancreas and duodenum tissues within the same individual, suggesting that intrapancreatic bacteria may migrate from the surrounding gut tract across the intestinal wall [72].…”
Section: Intratumor Microbiota Of Pancreatic Cancermentioning
confidence: 93%
“…The Fusobacterium species, a group of oral bacteria, were initially detected in PDAC tissues by Mitsuhashi et al [78] and were found to be independently associated with a worse patient survival probability. The intrapancreatic abundance of Fusobacterium species was found to be relatively higher in PDAC subjects than in noncancer controls [72]. Fusobacterium nucleatum elicited chemoresistance to 5-FU and oxaliplatin in CRC, targeting TLR4 and MyD88 immune signaling and activating the cancer autophagy pathway via downregulation of miR-18a* and miR-4802 [30].…”
Section: Intratumor Microbiota Of Pancreatic Cancermentioning
confidence: 95%
“…In their review, Goodman and Gardner (2018) summarize several compelling examples, such as increased Fusobacterium species associating with tumors in colon and Helicobacter pylori inducing lymphoma and gastric cancer. More recently, bacteria have been identified in pancreatic tissue in cancer patients (del Castillo et al, 2019) and have been shown to play a role in carcinogenesis in the pancreas (Pushalkar et al, 2018). Additional studies have also reported evidence that certain oral bacteria and periodontal disease associate with an increased risk in pancreatic cancer (Michaud et al, 2012;Fan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%